Penguatan Literasi Sejarah Peradaban Islam melalui Sosialisasi Dinasti Abbasiyah: Program Pengabdian Masyarakat Berbasis Edukasi Sejarah - Mubarok, Muhammad Mufti (Pakis Journal Institute, 2025)
This community service program aims to enhance Islamic historical literacy, particularly regarding the influence of the Abbasid Dynasty on the development of politics, culture, and scientific knowledge. The activities were carried out through public outreach, history reading–writing training, and the provision of educational modules for students and literacy communities in Bengkulu City. The selection of the Abbasid theme is based on the significance of this period as the golden age of Islamic civilization, which serves as an inspirational foundation for strengthening public understanding of history. The implementation methods included initial observation, preparation of learning materials, interactive training sessions, group discussions, and impact evaluation. The results of the program show an increased understanding of Abbasid history among participants, a growing interest in the study of Islamic history, and the establishment of independent learning groups in partner schools. This program is expected to serve as a community-based history education model that can be replicated in other regions.